Implementasi Kebijakan Kawasan Tanpa Rokok (KTR) di SMA Negeri 17 Medan - Khairatunnisa Khairatunnisa; Iska Putra Telaumbanua (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Introduction: Medan City Government has Regional Regulation No. 3 of 2014 concerning No-Smoking Area, the aim is to create a clean and healthy space and environment. In fact there are still those who violate the regulations of the Local Government where one of the teaching and learning process in SMA 17 Medan, there are still smoking. Objective:Research is descriptive qualitative. Research informants consisted of school principals, teachers, students and security guards. Results: The implementation of the No Smoking Area policy in SMA 17 Medan has not run optimally due to 4 factors, namely: Communication factors, lack of socializing the application of No-Smoking Area; the resource factor, the lack of facilities and infrastructure for the application of No-Smoking Area and the absence of specific guidelines as information for implementing the policy; Disposition factors, lack of commitment from policy implementers; and bireaucratic factors, there is no formation of policy making groups, no evaluation of the application of No-Smoking Area is carried out.Suggestion: The Medan City Education Office increased No-Smoking Area socialization, increased supervision, imposed sanctions on schools that did not implement No-Smoking Area. To the school, to increase No-Smoking Area socialization, apply strict sanctions and form a No-Smoking Area policy-making working group. Keywords: Implementation, No-Smoking Area.